1998
DOI: 10.2166/wst.1998.0014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the methods for determining the settling characteristics of sewage and stormwater solids

Abstract: In order to optimise the design and the management of sewer networks and settling tanks, there is a need to determine the settling velocity characteristics of sewage and stormwater solids. Devices and test methods for measuring settling velocities of these solids have been developed (Chebbo, 1992), (Michelbach and Wohrle, 1993) and (Tyack et al., 1993). In order to quantify the influence of the experimental procedure on the settling velocity grading curves, we have compared three selected methods (Cergrene, As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Over the years, several static settling columns have been developed, for example, Aston column (Tyack, Hedges, & Smisson, ), Umwelt‐ and Fluid‐Technik (UFT) column (Michelback & Wöhrle, ), CERGRENE protocol (Chebbo, ), U.S. EPA column (O’Connor et al, ), and the newer ViCAs protocol (Chebbo & Gromaire, ). The height of these settling columns varies between 0.2 and 1.8 m, with sample volumes ranging between 1 and 40 L. Also, some protocols include a sample preparation step applying a pretreatment such as sieving or settleable solids preselection (Aiguier et al, ; Lucas‐Aiguier, Chebbo, Bertrand‐Krajewski, Gagné, & Hedges, ). In addition, on several occasions, these methods have been compared and the results show different PSVD curves (Aiguier et al, ; Krishnappan et al, ; Lucas‐Aiguier et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several static settling columns have been developed, for example, Aston column (Tyack, Hedges, & Smisson, ), Umwelt‐ and Fluid‐Technik (UFT) column (Michelback & Wöhrle, ), CERGRENE protocol (Chebbo, ), U.S. EPA column (O’Connor et al, ), and the newer ViCAs protocol (Chebbo & Gromaire, ). The height of these settling columns varies between 0.2 and 1.8 m, with sample volumes ranging between 1 and 40 L. Also, some protocols include a sample preparation step applying a pretreatment such as sieving or settleable solids preselection (Aiguier et al, ; Lucas‐Aiguier, Chebbo, Bertrand‐Krajewski, Gagné, & Hedges, ). In addition, on several occasions, these methods have been compared and the results show different PSVD curves (Aiguier et al, ; Krishnappan et al, ; Lucas‐Aiguier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The height of these settling columns varies between 0.2 and 1.8 m, with sample volumes ranging between 1 and 40 L. Also, some protocols include a sample preparation step applying a pretreatment such as sieving or settleable solids preselection (Aiguier et al, ; Lucas‐Aiguier, Chebbo, Bertrand‐Krajewski, Gagné, & Hedges, ). In addition, on several occasions, these methods have been compared and the results show different PSVD curves (Aiguier et al, ; Krishnappan et al, ; Lucas‐Aiguier et al, ). Lucas‐Aiguier et al () pointed out that these differences are probably due to the different sizing of the columns.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of columns belonging to the first group include the U.S. EPA Column (Dalrymple et al 1975;O'Connor et al 2002), Aston Column of the Aston University in the U.K. , Umwelt-und Fluid-Technik Apparatus, Germany (also known as the Brombach column; Michelbach and Wöhrle 1993), and the Cergrene apparatus (Chebbo 1992;Aiguier et al 1996). While the individual columns differ in their design and operational procedures (Aiguier et al 1996(Aiguier et al , 1998, all suffer from a limitation of quiescent settling, which is not typical for actual CSO settling tanks. The need to account for settling under flow turbulence led to the development of a more complex apparatus incorporating an oscillating grid (Rasmussen and Larsen 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This proliferation of testing methods raises the question of how similar the settling velocity characterizations produced by these methods are, and consequently, a number of researchers conducted comparative studies (Aiguier et al 1996(Aiguier et al , 1998Tyack et al 1996;O'Connor et al 2002). Aiguier et al (1996) compared four columns (i.e., Aston Column, UFT column, Andreasen pipette and the Cergrene settling column) and observed that for the same sample, the different columns indicated different settling velocity distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation